2012
DOI: 10.4041/kjod.2012.42.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface anodization on stability of orthodontic microimplant

Abstract: ObjectiveTo determine the effect of surface anodization on the interfacial strength between an orthodontic microimplant (MI) and the rabbit tibial bone, particularly in the initial phase after placement.MethodsA total of 36 MIs were driven into the tibias of 3 mature rabbits by using the self-drilling method and then removed after 6 weeks. Half the MIs were as-machined (n = 18; machined group), while the remaining had anodized surfaces (n = 18; anodized group). The peak insertion torque (PIT) and the peak remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
0
28
0
4
Order By: Relevance
“…This is due to the increase of bone-implant contact by bone remodeling and bone maturation during the first 6 weeks. [16][17][18] Stability of orthodontic mini-implants was evaluated by measuring removal torque 13,22 and histomorphometric analysis was evaluated by measuring BIC. 23,24 Mechanical analysis showed no change in maximum removal torque or total energy with time lapse.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the increase of bone-implant contact by bone remodeling and bone maturation during the first 6 weeks. [16][17][18] Stability of orthodontic mini-implants was evaluated by measuring removal torque 13,22 and histomorphometric analysis was evaluated by measuring BIC. 23,24 Mechanical analysis showed no change in maximum removal torque or total energy with time lapse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that titanium implants have a reliable success rate due to their well-documented biocompatibility [811]. Various types of such implants are widely used today to substitute for missing teeth and to act as supporting retentive structures or anchorage devices [7, 1216].…”
Section: Introductionmentioning
confidence: 99%
“…It also improved adhesion, proliferation of osteoblastic cells and promoting osseointegration. [17][18][19] The resultant of such treatment was, 3 D bone formation around the MIs and greater bone to implants , contact which enhanced the stability of MIs. 19 The success rate in this study was 22 (81.5%) anodized mini-screw implants , while only 18 (66%) smooth surface minimplants were stable throughout the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The resultant of such treatment was, 3 D bone formation around the MIs and greater bone to implants , contact which enhanced the stability of MIs. 19 The success rate in this study was 22 (81.5%) anodized mini-screw implants , while only 18 (66%) smooth surface minimplants were stable throughout the treatment. The literatures reported different success rates, Tseng et al 20 reported success rate of 91% after examining the stability of 45 MIs used in orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation